2014
DOI: 10.1111/jipb.12155
|View full text |Cite
|
Sign up to set email alerts
|

Signaling events during initiation of arbuscular mycorrhizal symbiosis

Abstract: Under nutrient-limiting conditions, plants will enter into symbiosis with arbuscular mycorrhizal (AM) fungi for the enhancement of mineral nutrient acquisition from the surrounding soil. AM fungi live in close, intracellular association with plant roots where they transfer phosphate and nitrogen to the plant in exchange for carbon. They are obligate fungi, relying on their host as their only carbon source. Much has been discovered in the last decade concerning the signaling events during initiation of the AM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 126 publications
1
59
0
2
Order By: Relevance
“…Conversely, it has also been shown that many fungal pathogens are equipped with effectors to suppress chitin-triggered immunity or escape from the detection of fungal chitin by host receptors [6]. Recent findings also indicate that chitin-related molecules serve as a symbiotic signal in the interaction between arbuscular mycorrhizal fungi and host plants [7]. In this review, we focus on the plant-fungal interactions mediated by chitin and related molecules, which govern 'friend and foe' relationships between these organisms, and also the arms race for chitin-triggered immunity.…”
mentioning
confidence: 94%
“…Conversely, it has also been shown that many fungal pathogens are equipped with effectors to suppress chitin-triggered immunity or escape from the detection of fungal chitin by host receptors [6]. Recent findings also indicate that chitin-related molecules serve as a symbiotic signal in the interaction between arbuscular mycorrhizal fungi and host plants [7]. In this review, we focus on the plant-fungal interactions mediated by chitin and related molecules, which govern 'friend and foe' relationships between these organisms, and also the arms race for chitin-triggered immunity.…”
mentioning
confidence: 94%
“…The interaction between host plant and AMF begins with an exchange of signals well before physical contact occurs. Plant‐derived strigolactones (Nadal & Paszkowski ; Schmitz & Harrison ) as well as flavonoids (Scervino et al . , ; Steinkellner et al .…”
Section: Introductionmentioning
confidence: 99%
“…4; organisms. Likewise, it formed arbuscules as organs of reproduction (Makarian et al, 2013;Schmitz & Harrison, 2014;F. A. Smith & S. E. Smith, 2011), thus increasing the infection percentage.…”
Section: Discussionmentioning
confidence: 99%